2019
DOI: 10.1152/japplphysiol.00459.2019
|View full text |Cite
|
Sign up to set email alerts
|

Single-muscle fiber contractile properties in lifelong aerobic exercising women

Abstract: The purpose of this study was to examine the effects of lifelong aerobic exercise on single-muscle fiber performance in trained women (LLE; n = 7, 72 ± 2 yr) by comparing them to old healthy nonexercisers (OH; n = 10, 75 ± 1 yr) and young exercisers (YE; n = 10, 25 ± 1 yr). On average, LLE had exercised ~5 days/wk for ~7 h/wk over the past 48 ± 2 yr. Each subject had a vastus lateralis muscle biopsy to examine myosin heavy chain (MHC) I and IIa single-muscle fiber size and function (strength, speed, power). MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 68 publications
2
45
0
2
Order By: Relevance
“…Understandably, MAs are not entirely resistant to the effects of age and notable declines have been observed within older competitive athletes in overall performance (Lazarus & Harridge, 2017;Bagley et al 2019). Data at the single fibre level are less clear, suggesting older athletes have preserved contractile properties in the vastus lateralis, yet of type II fibres only (Power et al 2016b;Gries et al 2019). Moreover, as individual fibre power normalised to size appears to improve with age (Grosicki et al 2016), the neural input to muscle warrants greater research interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understandably, MAs are not entirely resistant to the effects of age and notable declines have been observed within older competitive athletes in overall performance (Lazarus & Harridge, 2017;Bagley et al 2019). Data at the single fibre level are less clear, suggesting older athletes have preserved contractile properties in the vastus lateralis, yet of type II fibres only (Power et al 2016b;Gries et al 2019). Moreover, as individual fibre power normalised to size appears to improve with age (Grosicki et al 2016), the neural input to muscle warrants greater research interest.…”
Section: Introductionmentioning
confidence: 99%
“…2016 b ; Gries et al . 2019). Moreover, as individual fibre power normalised to size appears to improve with age (Grosicki et al .…”
Section: Introductionmentioning
confidence: 99%
“…The same group of researchers analyzed women with an average age of 72 who trained in the last 48 years and found that lifelong training did not benefit type MHC I and IIa muscle fiber size but promoted adaptations of the contractile function that increased the strength of type I fibers and preserved the energy of type IIa fibers through different contractile mechanisms [ 109 ]. In addition, a greater intensity of training throughout life provided increased protection against the infiltration of adipose tissue in muscle [ 110 ].…”
Section: Exercise As a Time-conditioning Effectormentioning
confidence: 99%
“…One example situation from which more information may be obtained is study of Masters Athletes in whom muscle function may be well preserved into older age [ 112 ]. Such subjects still show an underlying age-related loss of muscle mass and function, but this extent of the loss appears reduced by the regular exercise [ 113 ].…”
Section: Testing the Hypothesismentioning
confidence: 99%